Pengembangan Lembar Kerja Peserta Didik (LKPD) untuk Melatihkan Keterampilan Literasi Sains Peserta Didik pada Materi Asam Basa Kelas XI - Suryani, Indah Ayu; Rusmini , Rusmini (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
This development research aims to describe the feasibility of a student worksheet on acid-base to train student's scientific literacy skills based on an analysis of validity, practicality, and effectiveness. This research uses Research and Development with a 4D model (Analysis, Design, Development, and Dissemination) but is limited to the development stage. Validity was obtained from the results of the assessment of 3 experts in chemistry education. The validity of the student worksheet is based on an assessment of the content, graphic, presentation, and linguistic aspects. The average score of the validity test results is 81%. Practicality and effectiveness data were obtained from a limited trial conducted in an Islamic school in Gresik Regency, East Java, on 27 students. At the trial stage, using the One Group Pretest-Posttest design. In the practicality test, it was observed from the student response questionnaire sheets and student activity sheets, including very practical criteria, each percentage was 92.45% and 92.26%. The pretest-posttest data of the student's cognitive knowledge and scientific literacy skills were tested for normality with SPSS. The data is normally distributed. Then t-test a result less than 0.05. It showed differences in the results of the pretest-posttest. The effectiveness of the student worksheet is based on increasing the n-gain score of cognitive knowledge and scientific literacy skills, obtaining a score of 85% and 86%, respectively, on the high criteria. Therefore, a student worksheet is appropriate to be used as a learning resource to train student's scientific literacy skills, making it easier to understand acid-base material and providing meaningful learning for students. Furthermore, it is expected that Indonesia's position in the literacy test will increase compared to previous years. Keywords: Worksheet, Scientific literacy skill, Acid base